The Mitigate+ approach to scaling CGIAR innovations toward low-emission food systems (webinar) - CGIAR Initiative on Low-Emission Food Systems (2023)
The CGIAR Initiative on Low-Emission Food Systems Initiative (Mitigate+) aims to contribute to low-emission food systems development and reduce net annual greenhouse gas emissions from food systems. Part of what we do is to identify and create the environment to scale CGIAR innovations with potential transformative effects, particularly in addressing the world’s single biggest challenge: climate change.